Metaphor of Transformation: Symbolic Representation of Tragedy in Loro Jonggrang Folklore and Pyramus-Thisbe - Afriansyah, Teddy; Kurniawan, Abimardha; Afdholy, Nadya (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
As in the Greek story of Pyramus-Thisbe and the Javanese folklore of Loro Jonggrang which symbolize a physical transformation as the concept of love tragedy. By using comparative literature studies, this research aims to 1) Analyze and describe the symbol of physical transformation in the stories Loro Jonggrang and Pyramus-Thisbe representing the concept of tragedy and 2) Analyzing and describing the cultural values underlying the symbols of tragedy that appear in Loro Jonggrang and Pyramus-Thisbe. The method used in this research is qualitative with a text analysis approach and refers to Clifford Geertz's symbolic anthropology theory. The results of the study found that, 1) There are several elements analyzed using several aspects of form comparison consisting of aspects of literary genre, narrative structure, language style, poetic form, theme & motif, and adaptation and intertextuality in the stories Loro Jonggrang and Pyramus-Thisbe. Then, 2) there is a cultural meaning behind the physical transformation of the two stories. In the Greek story Pyramus-Thisbe represent the concept of tragedy symbolized by the fruit of the mulberry tree. Meanwhile, the folk tales of Loro Jonggrang represent the concept of tragedy symbolized by the statue of Prambanan Temple.